Pillars of Nationality As Insight of The Archipelago - Ayla Nurindah Sari; Cinta Mutia Manullang; Wisnu Ramadani (Jurnal Pengetahuan Sosial dan Sejarah, 2025)
This article reviews the pillars of nationality as an insight into the archipelago, the pillars of nationality are a pillar so that a society can be firmly established and can feel comfortable, peaceful and also prosperous. In the pillars of nationality there are four pillars of Indonesian nationality contained in Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia and bhineka tunggal ika.